Helminthic infections in returning travelers and migrants with eosinophilia: Diagnostic value of medical history, eosinophil count and IgE. Issue 20 (November 2017) - Salzer, Helmut J.F.; Rolling, Thierry; Vinnemeier, Christof D.; Tannich, Egbert; Schmiedel, Stefan; Addo, Marylyn M.; Cramer, Jakob P.
Abstract: Objectives: Eosinophilia in travelers and migrants returning from the tropics is often associated with invasive helminthic infections. Total IgE is considered a useful additional diagnostic parameter; however, both parameters are also increased in various other non-helminthic diseases. Methods: We retrospectively evaluated travelers and migrants seen at our department between September 2007 and May 2014. Patients with an absolute eosinophil count ≥500 cells/μl were considered for further analyses. Results: Among 6618 returned travelers and migrants, 154 (2.3%) had a total eosinophil count ≥500 cells/μL. Of these, 71 patients (46%) were diagnosed with helminthic infection. In an additional 62 patients (40%) with eosinophilia a final diagnosis was found, including non-helminthic infections in 34 patients and non-infectious causes in 28 patients, while in 21 patients (14%) no diagnosis was made. Patients with helminthic infections had higher eosinophil counts than travelers and migrants with other diagnoses (median 981 vs. 710 cells/μl; p  = 0.001), while total IgE levels (n = 70; 172 vs. 152 kU/l; p = 0.731) were similar in both groups. Conclusion: Eosinophil count but not total IgE levels are associated with helminthic infections in returning travelers and migrants with eosinophilia. Our results do not support the use of total IgE to differentiate helminthic infections from other causes of eosinophilia in this population.